Formulasi Mikroenkapsulasi Protein dalam Poli(D,L-Laktida) dengan Teknik Penguapan Pelarut - Fitriani, Lili; Rachmawati, Heni; Suciati, Tri (Jurnal Sains dan Teknologi Farmasi, 2010)
Poly (D,L-lactide acid) has been used as scaffold and controlled release device for protein such as growth factor in tissue engineering. In this study, PDLLA microparticles were made and papain was used as model protein. Protein was encapsulated in microparticles using water-oil-water (W1/O/W2) and solid-oil-water (S/O/W) emulsification-solvent evaporation. Types of encapsulation methods and ratios of papain-PEG 20000 were observed in this study to provide the highest encapsulation efficiency. The entrapment efficiency made by W1/O/W2 method was 6,38%±0,025,  whilst S/O/W using ratios of papain-PEG 20000 1:1 ; 1:4 ; and 1:5 were 6,24%±0,91 ; 30,15%±1,66 and 60,67%±4,93, respectively. To conclude, S/O/W is the best method to encapsulate protein with highest entrapment efficiency.